Thinking for Soul, Reforming to Empower, and Cooperating to Strengthen Foundation: Responding to Implementation of Educational Reform of Civics and Political Science with Fuzzy Theory Algorithm - Wang, Caihua; Liang, Weidong; Wu, Shuxia (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Against the background of the new period of casting souls in Civics, empowering reforms, and strengthening foundations through cooperation, it is necessary to put the educational concepts and strategies of the Party and the government into practice in the process of deepening the educational reform of Civics and Politics courses.OBJECTIVES: This paper starts from the practical feasibility of the work and the conditions of the course design, with clear objectives, optimizing the teaching content, innovating and improving the teaching mode, and gradually forming effective strategies and methods of educational thought and policy.METHODS: This work examines and synthesizes the challenges and strategies of ideological and political education reform in the contemporary era, employing fuzzy theory and algorithmic approaches.RESULTS: It is concluded that the reform of the ideological and political curriculum is not only suitable for the development of students but also for the development of an era. Therefore, it is necessary to retain the content of all new textbooks, pay attention to the inclusion of ideological and political content in all textbooks, and ensure that there are scientifically sound and appropriate teaching materials for all teaching materials in order to contribute to the development of curriculum ideology and politics effectively.CONCLUSION: In the implementation process, it is necessary to improve the comprehensive quality of ideological and political course teaching, establish a sound ideological and political teaching system, and set up a comprehensive construction and educational collaboration mechanism. A multifactor ideological and political learning platform has been created to promote closer integration and interaction between theoretical learning and value orientation.
Keywords: ideological and political reform; problems and measures; ideological and political education; fuzzy theory algorithm